BUILDING AN APPLE IPAD MINI THEATER SYSTEM THROUGH IXTREAMER - Budi Berlinton Sitorus (Prosiding SNST Fakultas Teknik, 2012)
iPad as a tablet PC was designed to be used  as personal tablet PC. It offers several exciting features for users to browse, schedule, open documents, play game, listen to music, view photos, and more. Unfortunately, they only can be enjoyed personally. They are possible to extend  by the help of couple of peripherals such as Apple Digital AV adapter, Camera Connection Kit, Composite Cable, etc.  It may not result the great performance which involves limitation to iPad for wider use. The features offered are possible to extent in the purpose of using iPad not only as personal device but also usage of iPad for larger scope. Xtreamer technology, specifically iXtreamer, make it possible for iPad to enhance and build a mini theater system. Their combination will improve the perform of iPad. A research was conducted to  explore the limitations it has and find solutions.  By combining iPad and iXtreamer, an enhanced function of iPad will show how the iPad becomes a mini theater system. This system is extending the capability of iPad previously  as a personal device only  to a great system offering high multimedia features Keywords: tablet PC, iPad, mini theater system, multimedia, iXtreamer